Eksperimen Tipografi Hip-dut: Representasi Identitas Lokal Musik Dangdut Gen Z melalui Kecerdasan Buatan Visual - Dhika Purnama Putra; Carol Sebastian Hutauruk; Rana Syakirah Rinaldi; Dewi Pugersari; Arbi Cristional Lokananta (Universitas Budi Luhur, 2026)
This study examines the representation of local identity in Hip-dut music through digital typography as a form of visual expression among Generation Z in the era of digital popular culture. Hip-dut, as a fusion of dangdut, hip-hop, and Gen Z visual aesthetics, exists not only in the musical realm but also shapes a distinctive visual language through concert posters, song covers, and social media content. The central problem addressed in this research is the limited academic inquiry into Hip-dut typography as a representation of local cultural identity, particularly in relation to the use of visual artificial intelligence. This study employs a qualitative approach with a design experimentation method. Data were collected through observation of 90 Hip-dut visual artifacts, which were then analyzed using no-code visual artificial intelligence to identify dominant typographic patterns. The findings served as the foundation for exploring digital typeface design through generative AI technology, subsequently refined through manual processes. The experimental typefaces were evaluated via legibility and perception testing with a Gen Z audience. This research produced a prototype Hip-dut Display Typeface that represents the visual character of Hip-dut music, and demonstrates that collaboration between artificial intelligence and designer intuition can enrich typographic exploration rooted in local identity.